2017
DOI: 10.1002/ejoc.201700630
|View full text |Cite
|
Sign up to set email alerts
|

Optical Effect of Varying Acceptors in Pyrene Donor–Acceptor–Donor Chromophores

Abstract: Three donor–acceptor–donor (D–A–D) pyrene chromophores are described and compared by DFT computations. The two properties of low energy photon absorption and low energy electrochemical reduction are demonstrated through a pyrene framework. Altering the electron‐acceptor strength of the pyrene core by chemical oxidation or installation of a thiadiazole dioxide heterocycle results in the formation of D–A–D chromophores with absorption bands up to 900 nm and LUMO energy levels of approximately –4.1 eV vs. vacuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, their derivatives are not emissive and thus studies are missing on the influence on the excited state properties and how additional K-region substituents influence 2,7-substituted pyrenes. [40,41] In our previous reports we showed that the influence of a second amine donor at the 2,7-positions on the occupied orbitals is larger than that of a cyano or even Bmes 2 acceptor on the unoccupied orbitals and thus emission from the D-p-D derivative (I, Scheme 2) is further redshifted than the D-p-A compound (II, Scheme 2). Therefore, our initial objective was to utilize two julolidine-like donors at the 2,7-positions and add additional acceptors to the pyrene core to obtain a new class of D-p-A pyrene derivative with unparalleled photophysical properties such as red to NIR emission and interesting redox behavior.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, their derivatives are not emissive and thus studies are missing on the influence on the excited state properties and how additional K-region substituents influence 2,7-substituted pyrenes. [40,41] In our previous reports we showed that the influence of a second amine donor at the 2,7-positions on the occupied orbitals is larger than that of a cyano or even Bmes 2 acceptor on the unoccupied orbitals and thus emission from the D-p-D derivative (I, Scheme 2) is further redshifted than the D-p-A compound (II, Scheme 2). Therefore, our initial objective was to utilize two julolidine-like donors at the 2,7-positions and add additional acceptors to the pyrene core to obtain a new class of D-p-A pyrene derivative with unparalleled photophysical properties such as red to NIR emission and interesting redox behavior.…”
Section: Introductionmentioning
confidence: 92%
“…Hence, the electronic coupling V between the localized mixed valence states yields V = 1279 cm À1 for 7 + and I [15] 475 (hexane) 511 (hexane) -À0.18 (CH 2 Cl 2 ) + 0.26 (CH 2 Cl 2 ) 481 (THF) 525 (THF) II [15] 450 (hexane) 464 (hexane) À2.51 (THF) + 0.29 (THF) 462 (THF) 497 (THF) III [32] ---+ 0.14 (CH 2 Cl 2 ) + 0.38 (CH 2 Cl 2 ) IV [28] 453 (toluene) 482 (toluene) ---V [41] 630 (CHCl 3 ) -À0.67 (CHCl 3 ) + 0.39 (CHCl 3 ) -VI [40] 575 (CHCl 3 ) -À1.04 (CHCl 3 ) + 0.33 (CHCl 3 ) -VII [45] 455 (CH 2 Cl 2 ) 538 (CH 2 Cl 2 ) À1.43 (THF) --VIII [46] 435 (CH 2 Cl 2 ) 471 (CH 2 Cl 2 ) --- 2 , which shows that these compounds are class-II compounds, but lie close to the borderline between localized class-II and delocalized class-III compounds, as V is quite large. This result is also in line with the observed broad and asymmetric band shape.…”
Section: Spectroelectrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular methods for the calculation of dioxothiadiazole properties is standard and involve DFT with B3LYP hybrid functional and a 6-311G++(d,p) or 6-311G++(3df,3pd) basis set. As in the case of most organic molecules, it is fast and reliable in reproducing data for UV-vis and IR interpretation that closely resemble experimental results [ 21 , 42 , 45 , 51 , 59 , 60 ]. For EPR spectra simulations, usually a B98 hybrid functional is used instead.…”
Section: Structure and Geometrymentioning
confidence: 62%
“…Dioxothiadiazole-based electroactive molecules [27][28][29][30][31][32][33] and their complexes [34], on the other hand, are still underrepresented, despite their obvious advantages: easy reduction to a stable radical form, good coordination abilities (including bridging mode) and chemical tunability presented here for the first time. In 2011, Awaga et al studied [1,2,5]thiadiazole [3,4-f][1,10]phenanthroline 1,1-dioxide (L) in context of its electrochemical properties and synthesis of radical salts [35].…”
Section: Introductionmentioning
confidence: 96%